2010
DOI: 10.4236/jgis.2010.21009
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Statistical AOA Model Pertinent to Indoor Geolocation

Abstract: Abstract:A novel statistical angle-of-arrival (AOA) model for indoor geolocation applications is presented. The modeling approach focuses on the arrivals of the multipath components with respect to the line-of-sight (LOS) path which is an important component especially when indoor geolocation applications are considered. The model is particularly important for indoor applications where AOA information could be utilized for tracking indirect paths to aid in precise ranging in harsh and dense multipath environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Recently, much work has been conducted to model the AoA distribution in different multipath environments. AoA measurements by [9,10] in an indoor communication channel revealed that the AS has a Laplacian distribution. Another common angular spread profile includes uniform and Gaussian PDFs [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much work has been conducted to model the AoA distribution in different multipath environments. AoA measurements by [9,10] in an indoor communication channel revealed that the AS has a Laplacian distribution. Another common angular spread profile includes uniform and Gaussian PDFs [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…We used the average distance as the threshold of the distance determination for the stay point in the first step. The distance threshold was determined by the average distance between two adjacent points in the customer trajectory dataset, as shown in Equations (6) and (7) as follows:…”
Section: Distance Threshold Determinationmentioning
confidence: 99%
“…Therefore, research on indoor 2 of 22 positioning is currently a popular topic. Indoor positioning technology provides the TOA (time difference of arrival) based on the electromagnetic wave propagation time positioning technology [5,6], the AOA (angle of arrival) based on the incidence angle of electromagnetic waves [7,8], the TDOA based on the arrival of the frequency of magnetic wave positioning technology [9,10], signal strength based on RSSI (received signal strength indication) positioning technology [11,12], and the AP (access point) sensor signal strength based on positioning technology [13,14].…”
Section: Introductionmentioning
confidence: 99%